Neighbourhood greenness and depression among older adults. (August 2019) - Perrino, Tatiana; Lombard, Joanna; Rundek, Tatjana; Wang, Kefeng; Dong, Chuanhui; Gutierrez, Carolina Marinovic; Toro, Matthew; Byrne, Margaret M.; Nardi, Maria I.; Kardys, Jack; Szapocznik, José; Brown, Scott C.
Abstract : Background: Neighbourhood greenness or vegetative presence has been associated with indicators of health and well-being, but its relationship to depression in older adults has been less studied. Understanding the role of environmental factors in depression may inform and complement traditional depression interventions, including both prevention and treatment. Aims: This study examines the relationship between neighbourhood greenness and depression diagnoses among older adults in Miami-Dade County, Florida, USA. Method: Analyses examined 249 405 beneficiaries enrolled in Medicare, a USA federal health insurance programme for older adults. Participants were 65 years and older, living in the same Miami location across 2 years (2010–2011). Multilevel analyses assessed the relationship between neighbourhood greenness, assessed by average block-level normalised difference vegetative index via satellite imagery, and depression diagnosis using USA Medicare claims data. Covariates were individual age, gender, race/ethnicity, number of comorbid health conditions and neighbourhood median household income. Results: Over 9% of beneficiaries had a depression diagnosis. Higher levels of greenness were associated with lower odds of depression, even after adjusting for demographics and health comorbidities. When compared with individuals residing in the lowest tertile of greenness, individuals from the middle tertile (medium greenness) had 8% lower odds of depression (odds ratio 0.92; 95% CI 0.88, 0.96; P = 0.0004) and those from the high tertile (high greenness) had 16% lower odds of depression (odds ratio 0.84; 95% CI 0.79, 0.88; P < 0.0001). Conclusions: Higher levels of greenness may reduce depression odds among older adults. Increasing greenery – even to moderate levels – may enhance individual-level approaches to promoting wellness. Declaration of interest: None.